2011
DOI: 10.1097/mao.0b013e31820e6dc8
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Ménière's Disease With "On-Demand" Intratympanic Gentamicin Injections

Abstract: On-demand administration of intratympanic gentamicin provides an alternative treatment for medically refractory Ménière's disease. Moreover, the Kaplan-Meier analysis was useful to analyze recurrent manifestations, such as vertigo attacks in Ménière's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 14 publications
3
20
0
Order By: Relevance
“…Over the years, there has been a trend toward the use of smaller doses of gentamicin and/or longer intervals between injections. As a consequence, there has been a reduction of side effects such as hearing loss and posttreatment disability . In a 2‐year follow‐up study, we have already shown that there is a 50% chance of complete resolution of vertigo spells after one instillation of gentamicin, which is in accordance with other researchers …”
Section: Introductionsupporting
confidence: 91%
See 2 more Smart Citations
“…Over the years, there has been a trend toward the use of smaller doses of gentamicin and/or longer intervals between injections. As a consequence, there has been a reduction of side effects such as hearing loss and posttreatment disability . In a 2‐year follow‐up study, we have already shown that there is a 50% chance of complete resolution of vertigo spells after one instillation of gentamicin, which is in accordance with other researchers …”
Section: Introductionsupporting
confidence: 91%
“…A 24‐month period of time has been recommended by the American Academy of Otolaryngology Head‐and‐Neck Surgery guidelines for reporting results in MD. No recurrences were previously seen in the one that we are reporting …”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Improved experience on this treatment modality has made evident that ITGent works even in the absence of a complete vestibular deafferentation (2Y4, 8,9,15). As a result, ITGent dosage has progressively been reduced, and some authors remark that a therapeutic effect is produced after 1 or 2 single-shot applications, with the appreciable advantage of minimizing risk of hearing deterioration (2,3,8Y10,14,16).…”
Section: Intratympanic (It) Administration Of Gentamicin (Gent)mentioning
confidence: 98%
“…ITGent injection was administered within a variable period of time from 1 week to 3 weeks after 3D‐FLAIR MRI. A single‐shot administration protocol was attempted with additional injections administered on demand in the case of relapsing vertigo spells 9, 10. At least a 1‐month interval between the administrations was observed.…”
Section: Methodsmentioning
confidence: 99%